2022
DOI: 10.1016/j.jaci.2021.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Novel antibody cocktail targeting Bet v 1 rapidly and sustainably treats birch allergy symptoms in a phase 1 study

Abstract: Background: The efficacy of an allergen-specific IgG cocktail to treat cat allergy suggests that allergen-specific IgG may be a major protective mechanism elicited by allergen immunotherapy. Objectives: Extending these findings, we tested a Bet v 1-specific antibody cocktail in birch-allergic subjects. Methods: This was a phase 1, randomized, double-blind, study with 2 parts. Part A administered ascending doses of the Bet v 1-specific antibody cocktail REGN5713/14/15 (150-900 mg) in 32 healthy adults. Part B a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 45 publications
2
51
0
Order By: Relevance
“…The utility of this approach to achieve symptomatic relief in individuals with birch allergy has been realized in a proof-of-principle clinical study evaluating the ability of REGN5713/14/15 to block acute allergic symptoms triggered by nasal provocation with birch pollen extract. 64 Together with the positive results achieved in a similar clinical study using 2 distinct IgG mAbs REGN1908/09 that target the major cat allergen, Fel d 1, in patients with cat allergy, 21 our findings support the notion that passive administration of allergenspecific mAbs may possibly offer a new and more convenient treatment approach for allergy and presents the potential of establishing a repertoire of antiallergen therapeutics for personalized allergy management.…”
Section: Discussionsupporting
confidence: 70%
“…The utility of this approach to achieve symptomatic relief in individuals with birch allergy has been realized in a proof-of-principle clinical study evaluating the ability of REGN5713/14/15 to block acute allergic symptoms triggered by nasal provocation with birch pollen extract. 64 Together with the positive results achieved in a similar clinical study using 2 distinct IgG mAbs REGN1908/09 that target the major cat allergen, Fel d 1, in patients with cat allergy, 21 our findings support the notion that passive administration of allergenspecific mAbs may possibly offer a new and more convenient treatment approach for allergy and presents the potential of establishing a repertoire of antiallergen therapeutics for personalized allergy management.…”
Section: Discussionsupporting
confidence: 70%
“…20 This study provides evidence for the applicability of nanobodies for passive immunotherapy of allergy, similar to monoclonal antibodies as has been shown only recently. [18][19][20][21] Since nanobodies per se have a very short in vivo half-life, several strategies to extend the in vivo half-life of nanobody-based constructs have been developed. 46 As most appropriate formats, we consider to engineer bi-specific nanobodies with specificities against Bet v 1 and albumin due to its high abundance and long circulation in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it was recently demonstrated that large quantities of Bet v 1-specific monoclonal antibodies (i.e., 900 mg/patient) were needed to sufficiently inhibit allergen-induced mast cell degranulation during the entire birch pollen season. 20,21 Once reformatted, Bet v 1-specific nanobodies may represent an attractive cost-effective alternative to monoclonal antibodies worth to be tested for their clinical efficacy. Furthermore, passive administration of pre-selected formatted Bet v 1-specific blocking nanobodies may also be considered as more convenient treatment approach compared to anti-histamines which have to be applied every day and still bear some side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the possibilities is the administration of a so-called passive AIT under the form of antigen-specific immunosuppressive antibodies that have the ability of competing with IgE for allergen binding and functionally preventing the immediate hypersensitivity response. This hypothesis has been tested in both cat- and birch-allergic patients, receiving subcutaneous injections with a pre-selected allergen-blocking IgG against the respective major allergens showing beneficial results for over 2 months after only one injection ( 157 , 158 ). Because of the mucosal advantage of IgA over IgG, a similar therapeutic potential may lie in the local administration of isolated allergen-specific IgA, which has been shown to be effective in an in vivo mouse model of airway allergy ( 104 ).…”
Section: Future Perspectivesmentioning
confidence: 99%